Biocatalytic preparation and characterization of alternative substrate of MshB, a mycothiol pathway enzyme - Muneri, Ndivhuwo Olga (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.